2022
DOI: 10.35882/ijeeemi.v4i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tube Leakage of X-Ray Radiation Using Geiger Muller Sensor Equipped with Data Storage

Abstract: X-ray radiation (ionization) cannot be felt directly by the five human senses. Therefore, radiation monitoring is needed, one of which by using a survey meter. The purpose of this research is to directly monitor the level of radiation exposure and leakage of X-ray tube containers in the work area. This was done to ensure the safety and health of workers in the radiation transmission area, so that it is in accordance with the ALARA (As Low As Reasonably Achievable) principle, which is stipulated in the Decree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The front area of the tube was a common highest leak area of the tube. Utomo et al, shown from his research that the highest radiation leakage was from the front area which is proportional to this study [29]. From the data above, it can be interpreted that radiation leakage from x-ray tube is in line with previous research.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The front area of the tube was a common highest leak area of the tube. Utomo et al, shown from his research that the highest radiation leakage was from the front area which is proportional to this study [29]. From the data above, it can be interpreted that radiation leakage from x-ray tube is in line with previous research.…”
Section: Discussionsupporting
confidence: 88%
“…The smartphones count were 0.02 μGy/h, 0.16 μGy/h, and 0 μGy/h. The result was contradicted with the study conducted by Utomo et al which the lowest radiation leakage area was the rear [29]. The highest radiation count by surveymeter is at the front of the tube which was 21.14 μGy/h, as for the smartphones count were 2.32 μGy/h, 0.23 μGy/h, and 0.31 μGy/h.…”
Section: Discussionmentioning
confidence: 70%